2006 14th Annual IEEE Symposium on Field-Programmable Custom Computing Machines 2006
DOI: 10.1109/fccm.2006.52
|View full text |Cite
|
Sign up to set email alerts
|

Integrating FPGA Acceleration into the Protomol Molecular Dynamics Code: Preliminary Report

Abstract: We describe a new pipeline for computing non-bonded forces and its integration into the ProtoMol molecular dynamics (MD) code. There are several innovations: a novel interpolation strategy, including use of higher order terms; coefficient generation with orthonormal functions; the introduction of "semifloating point" numbering; and various issues related to system integration. As a result, we are able to model far more particle types, without relying on complex buffering, and obtain higher accuracy than previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…(Gu et al, 2006a) implemented MD on a Xilinx Virtex-II board, which demonstrated a speedup up to 88×. (Gu et al, 2006b;Gu et al, 2006c) integrated FPGA accelerated non-bonded forces calculation into ProtoMol MD code (Matthey et al, 2004). In (Gu and Herbordt, 2007), multigrid computation, which is an essential part of long-range force calculation, was implemented on FPGAs with a speed of 5× to 7×.…”
Section: Previous Work Of 3d Ffts On Fpgasmentioning
confidence: 99%
“…(Gu et al, 2006a) implemented MD on a Xilinx Virtex-II board, which demonstrated a speedup up to 88×. (Gu et al, 2006b;Gu et al, 2006c) integrated FPGA accelerated non-bonded forces calculation into ProtoMol MD code (Matthey et al, 2004). In (Gu and Herbordt, 2007), multigrid computation, which is an essential part of long-range force calculation, was implemented on FPGAs with a speed of 5× to 7×.…”
Section: Previous Work Of 3d Ffts On Fpgasmentioning
confidence: 99%